2016
DOI: 10.1002/jcp.25623
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Pathogenesis of Neurotrophic Keratitis: The Role of Corneal Nerves

Abstract: Neurotrophic keratitis (NK) is a rare degenerative disease of the cornea caused by trigeminal nerve damage, which leads to loss of corneal sensitivity, corneal epithelium breakdown, and poor healing. Though extremely uncommon, NK is increasingly recognized for its characteristics as a distinct and well-defined clinical entity rather than a rare complication of various diseases that can disrupt trigeminal innervation. Indeed, the defining feature of NK is loss of corneal sensitivity, and its clinical findings d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
128
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 78 publications
0
128
1
1
Order By: Relevance
“…Despite its clinical relevance, our knowledge about corneal nerve regeneration following injury and diseases such as neurotrophic keratitis remains sub-optimal 10 . Many studies have demonstrated interplay between immune cells and corneal nerves (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its clinical relevance, our knowledge about corneal nerve regeneration following injury and diseases such as neurotrophic keratitis remains sub-optimal 10 . Many studies have demonstrated interplay between immune cells and corneal nerves (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing corneal resurfacing in WT animals to those with constitutive loss of NEP activity, a potential confounding factor is the increased density of corneal innervation observed in NEP −/− mice. Because corneal nerves produce epitheliotrophic factors that promote physiological renewal as well as wound healing 43 45 , accelerated corneal wound healing in NEP −/− mice may be related to increased innervation at baseline. However, pharmacologic NEP inhibition with thiorphan also promoted epithelial recovery in WT mice within one week of corneal injury, an interval too brief for extensive reinnervation.…”
Section: Discussionmentioning
confidence: 99%
“…Several excellent recent reviews [6][7][8][9] indicate that a large number of endogenous regulators are involved in regeneration of damaged corneal nerves ( Figure 3A). These corneal neurotrophins, guidance factors, inflammatory mediators, and hormones are important because they have been, or may be considered in the future, as the biochemical basis for drugs promoting nerve regeneration.…”
Section: Regulators Of Corneal Nerve Regenerationmentioning
confidence: 99%
“…Since systemic treatments (subcutaneous injection, intracerebro-ventricular infusion) were associated with hyperalgesia and back pain, current efforts have been directed towards gene therapy or topical application of NGF. Possibly one of the best studied has been the use of topical NGF against neurotrophic keratitis (NK) [8].…”
Section: Part Ii: Corneal Nerve Regeneration Using Drugs Based On Endmentioning
confidence: 99%